Analisis Faktor Pengendali Konflik Keagenan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi - Rita Amelinda (Jurnal Manajemen, 2018)
The purpose of this research is to measure the influence between agency conflict factors to the value of the firm with dividend policy as the moderating variable. Some of the variables which are used in this research such as the Free Cash Flow Ratio, Leverage, Return on Assets, GCG's Implementation (CGPI), Dividend Policy,  and Value of The Firm (Tobin's Q). This research sample consisted of 126 observations which are the listed company in Indonesia Stock Exchange (IDX) during the 2008-2014 period and they also are the company with the best GCG index. The results showed that Free Cash Flow Ratio, Leverage, Return on Asset, GCG's Implementation (CGPI), Dividend Policy have significant effects simultaneously on the Value of The Firm (Tobin's Q). While in partial, only GCG's Implementation (CGPI) doesn't have a significant effect on the value of The Firm (Tobin's Q). On the other hand, dividend policy significantly moderated the influence of the other 4 independent variables on the value of the firm.